Humoral Immunodeficiency with Hypotonia, Feeding Difficulties, Enteropathy, and Mild Eczema Caused by a Classical FOXP3 Mutation - Tuijnenburg, Paul; Cuadrado, Eloy; Bosch, Annet M.; Kindermann, Angelika; Jansen, Machiel H.; Alders, Marielle; van Leeuwen, Ester M. M.; Kuijpers, Taco W. (Frontiers in Pediatrics, 2017)
We describe here the case of a boy who presented with pulmonary infections, feeding difficulties due to velopharyngeal insufficiency and gastroesophageal reflux, myopathy and hypotonia soon after birth. Later he was also found to have an elevated immunoglobulin (Ig) E, mild eczema and was diagnosed with inflammatory bowel disease. Further immunological screening at the age of seven years showed low B and NK cell numbers but normal CD4+ and CD8+ T cells and notably, normal numbers of CD4+ regulatory T (Treg) cells. Serum IgG, IgA and IgM were low-normal but he had a deficient response to a pneumococcal polysaccharide vaccine and thus a humoral immunodeficiency. To our surprise, whole exome sequencing revealed a mutation in FOXP3, encoding an essential transcription factor for the development and function of Treg cells. This classical mutation is associated with Immune dysregulation, Polyendocrinopathy, Enteropathy, X-linked (IPEX) syndrome. Further in vitro studies indeed showed defective function of regulatory T cells despite normal FOXP3 protein expression and nuclear localization. The boy underwent hematopoietic stem cell transplantation at the age of eleven and despite the temporary development of diabetes while on prednisone is now doing much better, IgE levels have declined, and his fatigue has improved. This case illustrates that a classical pathogenic mutation in FOXP3 can lead to a clinical phenotype where the diagnosis of IPEX syndrome was never considered because of the lack of diabetes and the presence of only mild eczema, in addition to the normal regulatory T cell numbers and FOXP3 expression.